Microstructure and Density of Sintered ZnO Ceramics Prepared by Magnetic Pulsed Compaction - Ji-Woon Lee; Changhyun Jin; Soon-Jig Hong; Soong-Keun Hyun (Advances in Materials Science and Engineering)
Three different sintered ZnO ceramics were prepared by magnetic pulsed compaction (MPC) and other conventional methods. The microstructures of the sintered ZnO ceramics prepared by MPC at sintering temperatures ranging from 900 to 1300°C showed a homogeneous grain growth compared to those of the samples prepared using other methods under the same sintering conditions. This implies that interpowders and/or intergrains can induce the minimization of wall friction effect because of the application of a high compaction pressure for a short process time in the MPC method. In addition, the microstructure of the sample obtained using the cold isostatic pressing method showed the presence of heterogeneous regions, indicating its low quality even though the densities of the three different samples were almost similar in the range of 97–99% at sintering temperatures of 900, 1100, and 1300°C. Therefore, different methods used for the compaction of ZnO ceramics may result in different microstructural and physical properties of the product.